Short pulse generation in solid state lasers by a novel passive technique - Martinez, O. E., author; Marconi, Mario Carlo, author; Diodati, F. P., author; Elsevier Science Publishers B. V., publisher (Colorado State University. Libraries, 1987)
A novel passive Q-switching technique based on self-focusing is studied theoretically and experimentally. In this paper we present results obtained with a simple aberrationless gaussian model that describes the short pulse generation dynamics for different cavity configurations and different nonlinear characteristics of the focusing medium. Experimental results are also presented that are in good agreement with the predictions of the theoretical model. Preliminary results in ultrashort pulse generation are also presented.